2000
DOI: 10.1111/j.1582-4934.2000.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

New molecular mediators in tumor angiogenesis

Abstract: Angiogenesis is essential for tumor growth and progression. It has been demonstrated that tumor growth beyond a size 1 to 2 mm 3 requires the induction of new vessels. Angiogenesis is regulated by several endogenous stimulators and inhibitors of endothelial cell migration, proliferation and tube formation. Under physiological conditions these mediators of endothelial cell growth are in balance and vessel growth is limited. In fact, within the angiogenic balance endothelial cell turnover is sufficient to mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 59 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…Angiogenesis is a critical factor in facilitating increased tumor growth and progression in many tumors, including melanoma. [4][5][6][7][8][9][10][11][12][13] Factors important in regulating angiogenesis can be detected in surgical melanoma excisions and may reflect tumor progression to more tumorigenic melanomas with poor prognosis. [14][15][16] Many factors influence angiogenesis, most prominently, vascular endothelial growth factor (VEGF) stimulates angiogenesis through the expression of growth factors, adhesion molecules, proteases, and protease receptors 9,17 and has been observed to have importance in MM progression.…”
mentioning
confidence: 99%
“…Angiogenesis is a critical factor in facilitating increased tumor growth and progression in many tumors, including melanoma. [4][5][6][7][8][9][10][11][12][13] Factors important in regulating angiogenesis can be detected in surgical melanoma excisions and may reflect tumor progression to more tumorigenic melanomas with poor prognosis. [14][15][16] Many factors influence angiogenesis, most prominently, vascular endothelial growth factor (VEGF) stimulates angiogenesis through the expression of growth factors, adhesion molecules, proteases, and protease receptors 9,17 and has been observed to have importance in MM progression.…”
mentioning
confidence: 99%
“…Other functions of Mk expression may be regulated through the catecholamine and/or renin-angiotensin pathways as well; Mk −/− mice have reduced neointima formation in restenosis injury models that is reversible by systemic administration of MK (Horiba et al, 2000) and antisense Mk oligodeoxyribonucleotides suppress neointima formation after injury (Hayashi et al, 2005). Furthermore, MK and PTN also are known to stimulate angiogenesis in vivo (Chauhan et al, 1993;Yeh et al, 1998;Zhang and Deuel, 1999;Beecken et al, 2000;Mashour et al, 2001;Pufe et al, 2003;Christman et al, 2005), indicating again roles of both MK and PTN in vascular function and suggesting that MK and PTN may then be targets for therapy to suppress the abnormal angiogenesis associated with different diseases in which neo-angiogenesis contributes to the pathological progression of the disease itself. Recent evidence points the critical role in angiogenesis of the renin-angiotensin system (Yoshiji et al, 2002;Escobar et al, 2004;Lindberg et al, 2004), suggesting that MK and PTN signaling may be important in the angiogenic phenotype associated with different malignancies that express the constitutively active Mk and/or Ptn genes (Deuel et al, 2002) through regulation of the renin-angiotensin pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Angiopoietins bind to the Tie family of receptors, which can be found on the endothelial cell membrane surface, and mediate sprout formation and branching (Papetti and Herman, 2002). Both Ang-1 and Ang-2, the two main members of the family, have antagonistic functions: Ang-1 instigates sprout formation and Ang-2 inhibits it; see Beeken, Kramer and Jonas (2000) for an excellent review. Although it may seem at first glance that Ang-2 is an inhibitor of angiogenesis, in tumour-induced angiogenesis it has been shown that Ang-2 in conjunction with VEGF actually facilitates neovascularization because its action renders the recipient endothelial cells more sensitive to VEGF (Maisonpierre et al, 1997).…”
Section: Molecular Species In Angiogenesismentioning
confidence: 98%